Entrepreneurship Training for MSMEs to Increase Income - Kwartawaty, Nana Noviada; Sari, Deasy Virka; Jona, Resa Nirmala (Devotion : Journal of Research and Community Service, 2023)
Micro, small and medium enterprises (MSMEs) are an important sector in the Indonesian economy, because they can create jobs and improve income distribution. However, many MSMEs experience difficulties in gaining access to markets and developing their businesses due to a lack of skills and knowledge in the field of entrepreneurship. This study aims to determine the effectiveness of entrepreneurship training for MSMEs in increasing income. This study used qualitative research methods. Data collection techniques were carried out by interviews and literature studies. The results of the study show that entrepreneurship training for Micro, Small and Medium Enterprises (MSMEs) is effective in increasing income. In the study, MSMEs who attended entrepreneurship training showed a significant increase in their income compared to MSMEs who did not attend training. This is because entrepreneurship training equips business actors with the skills and knowledge needed to increase the efficiency and productivity of their businesses, as well as opens opportunities to expand networks and markets. In addition, entrepreneurship training also helps increase the confidence and motivation of business actors, so that they are better prepared and able to face challenges in developing their businesses. Therefore, entrepreneurship training can be one of the key factors in increasing MSME income and supporting economic growth at the local and national levels.